A systematic review of commercial serological antibody detection tests for the diagnosis of extrapulmonary tuberculosis. Issue 10 (3rd August 2007) - Steingart, Karen R; Henry, Megan; Laal, Suman; Hopewell, Philip C; Ramsay, Andrew; Menzies, Dick; Cunningham, Jane; Weldingh, Karin; Pai, Madhukar
Abstract : Conventional diagnostic tests for tuberculosis have several limitations and are often unhelpful in establishing the diagnosis of extrapulmonary tuberculosis. Although commercial serological antibody based tests are available, their usefulness in the diagnosis of extrapulmonary tuberculosis is unknown. A systematic review was conducted to assess the accuracy of commercial serological antibody detection tests for the diagnosis of extrapulmonary tuberculosis. In a comprehensive search, 21 studies that reported data on sensitivity and specificity for extrapulmonary tuberculosis were identified. These studies evaluated seven different commercial tests, with Anda-TB IgG accounting for 48% of the studies. The results showed that (1) all commercial tests provided highly variable estimates of sensitivity (range 0.00–1.00) and specificity (range 0.59–1.00) for all extrapulmonary sites combined; (2) the Anda-TB IgG kit showed highly variable sensitivity (range 0.26–1.00) and specificity (range 0.59–1.00) for all extrapulmonary sites combined; (3) for all tests combined, sensitivity estimates for both lymph node tuberculosis (range 0.23–1.00) and pleural tuberculosis (range 0.26–0.59) were poor and inconsistent; and (4) there were no data to determine the accuracy of the tests in children or in patients with HIV infection, the two groups for which the test would be most useful. At present, commercial antibody detection tests for extrapulmonary tuberculosis have no role in clinical care or case detection.